Insignificant events in the life of a cactus ebook - Bowling, Dusti (Life of a Cactus, 2017)
"Aven is a perky, hilarious, and inspiring protagonist whose attitude and humor will linger even after the last page has turned." —School Library Journal (Starred review) Aven Green loves to tell people that she lost her arms in an alligator wrestling match, or a wildfire in Tanzania, but the truth is she was born without them. And when her parents take a job running Stagecoach Pass, a rundown western theme park in Arizona, Aven moves with them across the country knowing that she'll have to answer the question over and over again. Her new life takes an unexpected turn when she bonds with Connor, a classmate who also feels isolated because of his own disability, and they discover a room at Stagecoach Pass that holds bigger secrets than Aven ever could have imagined. It's hard to solve a mystery, help a friend, and face your worst fears. But Aven's about to discover she can do it all . . . even without arms. Autumn 2017 Kids' Indie Next Pick Junior Library Guild Selection Library of Congress's 52 Great Reads List 2018